Firm size and society: The link between firm size, job outcomes, and political attitudes - Sinisa Hadziabdic; Sebastian Kohl (Max Planck Institute for the Study of Societies, 2024)
Given the recent reconcentration of the economy in many private industries, the impact of working in firms of different sizes on occupational and political outcomes is of renewed interest. Using micro-level data for the US and Germany, two most dissimilar cases in terms of labor market and political institutions, we show that large firms provide substantially more material and welfare benefits to their workers, while small firms are characterized by the highest job satisfaction and more harmonious relational dynamics. Workers in medium-sized firms appear to be "betwixt and between," being worst off in many dimensions, thus contradicting utopias of medium-sized-firm capitalism. Within firms of similar size, we also document a significant polarization between employers' and their employees' job experiences and political views. Given the number of waking hours spent in the workplace, the firm, hitherto a neglected locus of social sorting and socialization through which the economy shapes society, should figure more prominently in economic sociology research. – – Angesichts der jüngsten Re-Konzentration der Wirtschaft in vielen privaten Sektoren rücken die Auswirkungen der Arbeit in Unternehmen unterschiedlicher Größe auf gesellschaftliche Zusammenhänge erneut in den Mittelpunkt des Interesses. Anhand von Mikro- ebene-Daten für die USA und Deutschland, zwei Länder, die sich in Bezug auf den Ar- beitsmarkt und die politischen Institutionen stark unterscheiden, zeigen wir, dass große Unternehmen ihren Arbeitnehmenden wesentlich mehr materielle und soziale Leistungen bieten, während sich kleine Unternehmen durch die höchste Arbeitszufriedenheit und eine harmonischere Beziehungsdynamik auszeichnen. Arbeitnehmende in mittelständischen Unternehmen scheinen hingegen "zwischen den Stühlen zu sitzen" und in vielerlei Hinsicht am schlechtesten gestellt zu sein, was den Verheißungen des Mittelstandskapitalismus widerspricht. In Unternehmen ähnlicher Größe dokumentieren wir auch eine signifikante Polarisierung zwischen den beruflichen Erfahrungen und den politischen Ansichten der Arbeitgebenden und ihrer Arbeitnehmenden. In Anbetracht der am Arbeitsplatz verbrachten Lebenszeit sollte das Unternehmen als Ort der sozialen Selektion und der Sozialisierung, durch den die Wirtschaft die Gesellschaft prägt, stärker in den Blick wirtschaftssoziologischer Forschung genommen werden.
hdl:21.11116/0000-0010-0729-9
Keywords: 300; company size; Germany; job outcomes; political attitudes; USA; Arbeitsplatzqualität; Deutschland; politische Einstellungen; Unternehmensgröße; USA